Optimasi Kombinasi Karagenan dan Gelatin dalam Formulasi Permen Jelly Jagung Manis - Chusnur Rosyidah Rosyidah; Deny Utomo Utomo (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
Sweet corn is a cereal crop that serves as a source of carbohydrates and protein after rice; however, its utilization as a functional food remains limited, as most corn is used for animal feed. One alternative processing method is jelly candy, a type of soft candy favored by various age groups. The quality of jelly candy is strongly influenced by the type and concentration of gelling agents, particularly gelatin and carrageenan; therefore, appropriate formulation is required to obtain optimal physicochemical and sensory characteristics. This study aimed to optimize the formulation of sweet corn–based jelly candy through variations in gelatin and carrageenan concentrations. A factorial Completely Randomized Design (CRD) was applied with two factors: gelatin concentration (11 and 22 g) and carrageenan concentration (10, 15, and 20% of sweet corn extract), resulting in six treatment combinations with three replications. The analyzed parameters included moisture content, ash content, antioxidant activity, hardness value, and sensory attributes (color, aroma, texture, and taste). Data were analyzed using Analysis of Variance (ANOVA) followed by Tukey’s test at a 95% confidence level. The results showed that the optimum formulation was obtained at treatment G2K1 (22 g gelatin and 10% carrageenan), yielding a moisture content of 22.30%, ash content of 3.02%, antioxidant activity of 69.69 ppm, hardness value of 26.86 N, and sensory scores classified as liked.